A meta-analysis of cross cultural risk markers for intimate partner violence. (November 2016) - Mallory, Allen B.; Dharnidharka, Prerana; Deitz, Sharon L.; Barros-Gomes, Patricia; Cafferky, Bryan; Stith, Sandra M.; Van, Kimberly
Abstract: The majority of IPV research has originated from western countries and neglected to examine cultural influences. We meta-analyzed the strength of various well-established risk markers (demographic, individual-level and relational) for male-perpetrated IPV across different cultures. Using Hofstede, Hofstede, and Minkov's (2010) individualism scale, we grouped studies from countries into individualist and collectivist categories, and then accounted for the influence of the large number of U.S.-based studies, by creating 3 groups: U.S., Individualistic, and Collectivist. Risk markers across collectivist and U.S. groups had similar effect sizes across while risk markers in the U.S. had larger effect sizes than those found in the international individualist countries. Our findings suggest that if a comprehensive understanding of IPV perpetration is to be achieved, cultural context cannot be ignored. Highlights: Cultural context is important in understanding IPV risk markers. Markers in US/collectivist countries are more similar than US/individualist countries. Emotional abuse and control were strongest risk markers in all groups. Differences between groups were found for relationship and family risk markers.